Zhongguo li shi chang shi = common knowledge about Chinese history (Gao deng jiao yu chu ban she, 2007)
Common knowledge about Chinese history is an impressive introduction to China's long history beginning around Primitive Society till Opium War and up to the rise of Modern China. The book falls into three parts: Period before the Opium War of 1840, Modern Period and Contemporary Period. The whole book is strung together with abundant interesting historical stories about different dynasties, historical events and figures in ancient and modern China. It is a valuable primer in Chinese history, serving also as a useful Chinese textbook for overseas Chinese and foreign friends.